A National Study of Medical Students' Attitudes Toward Self-Prescribing and Responsibility to Report Impaired Colleagues. (April 2015) - Dyrbye, Liselotte N.; West, Colin P.; Satele, Daniel; Boone, Sonja; Sloan, Jeff; Shanafelt, Tait D.
<x xml:space="preserve">Abstract</x> Purpose The authors investigated medical students' attitudes about appropriate prescribing behaviors, their personal responsibility to report impaired colleagues, and what factors may influence these beliefs. Method The authors conducted a cross-sectional study of U.S. medical students in 2012 to assess attitudes about appropriate prescribing behaviors and responsibility to report impaired colleagues, and to explore relationships between prescribing beliefs and burnout, depression, and alcohol abuse/dependence. Chi-square test and multivariate logistic regression were performed. Results Of 12, 500 medical students invited to participate, 4, 402 (35%) completed surveys. Believing it is appropriate to prescribe an antidepressant to self or spouse was rare (<10%) in comparison with believing it is appropriate to prescribe an antibiotic for oneself (34.5%) or a spouse (57.7%). In multivariate analysis, students with burnout were more likely to agree that each of the inappropriate prescribing behaviors was acceptable (ORs 1.15–1.51). Students with burnout were less likely to believe they had a personal responsibility to report colleagues with impairment due to alcohol or substance use (OR 0.87). Students personally experiencing symptoms of depression were less likely to believe medical students should report colleagues impaired by mental health problems (OR 0.72). Similarly, students with alcohol abuse/dependence were less likely to believe they had a duty to report colleagues impaired by alcohol/substance use (OR 0.55). Conclusions Suboptimal attitudes about prescribing and personal responsibility to report impaired colleagues are common among medical students. Suboptimal attitudes are associated with personal distress, further evidence of a link between personal distress and professionalism.